The market imperative segmentation and change in higher education - Zemsky, Robert 1940-; Shaman, Susan (Reforming higher education: innovation and the public good, 2017)
"It is no surprise that college tuition and student debt are on the rise. Universities no longer charge tuition to simply cover costs. They are market enterprises that charge whatever the market will bear. Institutional ambition, along with increasing competition for students, now shapes the economics of higher education. In The Market Imperative, Robert Zemsky and Susan Shaman argue that too many institutional leaders and policymakers do not understand how deeply the consumer markets they promoted have changed American higher education. Instead of functioning as a single integrated industry, higher education is in fact a collection of segmented and more or less separate markets. These markets have their own distinctive operating constraints and logics, especially regarding price. But those most responsible for federal higher education policy have made a muck of the enterprise, while state policymaking has all but disappeared, the victim of weak imaginations, insufficient funding, and an aversion to targeted investment. Chapter by chapter, The Market Imperative draws on new data developed by the authors in a Gates Foundation-funded project to describe the landscape: how the market for higher education distributes students among competing institutions; what the job market is looking for; how markets differ across the fifty states; and how the higher education market determines the kinds of faculty at different kinds of institutions. The volume concludes with a three-pronged set of policies for making American higher education mission centered as well as market smart. Although there is no "one-size-fits-all" approach for reforming higher education, this clearly written book will productively advance understanding of the challenges colleges and universities face by providing a mapping of the configuration of the market for an undergraduate education"...